A collection development policy for Dr. Yanga's Colleges, Inc. Basic Education Library (DYCI-BEL) - Dela Cruz, Kevin Dhale S.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2015)
A collection development policy (CDP) is an integral component every school library must-have. By having a concrete CDP, the library will ensure the maintenance of a balanced collection that will substantially answer the information needs of its patrons. Dr. Yanga's Colleges, Inc. Basic Education Library (DYCI-BEL), in light of its parent institution's educational advancements and achievements, does not have its own CDP that will ensure an updated, well-balanced, and responsive in-house collection. Thus, this study aimed to formulate a well-written CDP for the BEL by performing a community needs analysis.
Guided by the theory of Evans and Saponaro's Information Needs Theory, the study focused on the assessment of user needs of the BEL-the students and faculty members of the Basic Education department (i.e. the Grade School and High School departments). Data were gathered from selected respondents through survey and interviews in order to assess their insights about the library collections. Furthermore, an institutional analysis was performed through document analysis on the school and library objectives, along with the curriculum used by the institution. Lastly, the chief librarian and the library staff were interviewed as part of library analysis. Reports from the library such as the collection density and library policies were also examined.
After the analysis and interpretation of data, the study revealed that 87% to 95% of the high school population were satisfied with the collections supporting their recreational and information needs while 49% to 62% were satisfied with the academic and curricular support given by the library collections. Suggestions and recommendations from the community include more efficient organization of books, addition of books on all subject areas and increase in the library staff. Likewise, the majority of the faculty members in both grade school and high school departments perceived the collections as inadequate in supporting the curricular needs of the students. Moreover, the library collections were not balanced; mostly focusing on fiction and non-fiction books. Finally, the library failed to meet the Department of Education standards for school libraries as part of the benchmarking process. Also, the library was not participating in any library linkages and networking.
Thesis (Bachelor of Library and Information Science)
Keywords: Collection development (Libraries) -- Philippines -- Bulacan